MEMBANGUN DIALOG INTERRELIGIUS ANTARUMAT BERAGAMA DI KOTA MALANG - Kristianto, Daniel; Aliano, Yohanes Alfrid (Bahasa Indonesia, 2024)
The aim of this research is to identify and analyze further the importance of dialogue and tolerance among religious communities, particularly in the city of Malang. For the author, the topic addressed in this writing is highly contextual, especially in fostering dialogue amidst religious pluralism. The lack of understanding of the values of tolerance and interreligious dialogue often provokes the emergence of intolerant attitudes among religious communities. In the writing entitled “Building Interreligious Dialogue Among Religious Communities in the City of Malang”. The author is interested in pointing this topic because the community in the city of Malang highly upholds the value of tolerance, which is evident in their perspective of accepting and respecting others of different religions. In this regard, tolerance can be achieved through dialogue. One of the methodologies used in this research is through interfaith dialogue from the perspective of Armada Riyanto, supported by the documents of the Church Nostra Aetate regarding interfaith dialogue. This paper is expected to explode the enthusiasm of all sectors in building dialogue among religious communities. This study ultimately concludes that interfaith dialogue will encourage a sense of brotherhood among religious communities and ultimately lead to an encounter with Almighty God.